Issues and Indicators of Meat Sector in India - Naveena, B. M.; Muthukumar, M.; Banerjee , Rituparna (Journal of Meat Science, 2019)
State-of-the-art technological interventions has resulted in transformation of unorganized and unscientific chicken farming practice in India to a highly successful commercial production system. Production and processing of milk in India has also seen a quantum leap in the last decade. However, few successful models observed in certain livestock/poultry commodities could not be replicated in other areas. Hence, identification of potential commodities and their commercial exploitation will pave the way for doubling farmer’s income. Effective interventions like reducing the mortality rate, better biosecurity, creation of disease free zones, minimizing the post-harvest losses, linking small producers to market, increased value addition and further processing, exploiting natural, organic, minimally processed, seasonal, fresh and locally grown sentiments will augment the farmer’s income. Assistance to farmers/farms to build production model in line with global GAP for ensuring safe, nutritious, traceable and affordable products to consumers.